Bioactive compounds profile and extraction yields in coffee (Coffea arabica L.) by-products: A comparative analysis using ethanol, methanol and acetone - Jiménez Gutiérrez, Yamileth Milena (2025)
Coffee beverages are consumed worldwide and produce considerable quantities of by-products from industrial processing every year. The present study identified 20 bioactive compounds in fresh coffee (Coffea arabica L.) husk and mucilage extracts from industrial processing. Ultra-high performance liquid chromatography coupled with diode array detection and triple quadrupole mass spectrometer (UHPLC-DAD-TQ/MS) was used for the profile of phytochemicals. Using ethanol (EtOH) as a green solvent, the extraction efficiency was compared with acetone and methanol (MeOH). Higher concentrations of Hydroxybenzoic Compounds (HBC) were found in husk than in mucilage and can be efficiently extracted with EtOH at 70, 80 and 90 %, with no significant differences with MeOH and acetone. Vanillic acid can be efficiently extracted from husk when 80 and 90% EtOH is used. Rutin, an important non-anthocyanin Flavonoid Compound (FC) due to its health benefits, can be extracted at all concentrations of EtOH with equal results compared to acetone and MeOH. Ethanol seems to be a promissory ¨green¨ solvent for extracting phenolic compounds, achieving similar extraction yields when compared to acetone and MeOH. The coffee husk and mucilage extracts could be used in the food, pharmaceutical and other industries.